Inductive Reasoning and Semantic Web Search - d'Amato, C; Esposito, F; Fanizzi, N; Fazzinga, B; Gottlob, G; Lukasiewicz, T (ACM Press, 2010)
Extensive research activities are recently directed towards the Semantic Web as a future form of the Web. Consequently, Web search as the key technology of the Web is evolving towards some novel form of Semantic Web search. A very promising recent approach to such Semantic Web search is based on combining standard Web search with ontological background knowledge and using standard Web search engines as the main inference motor of Semantic Web search. In this paper, we propose to further enhance this approach to Semantic Web search by the use of inductive reasoning. This adds the important ability to handle inconsistencies, noise, and incompleteness, which often occur in distributed and heterogeneous environments, such as the Web. We report on a prototype implementation of the new approach and extensive experimental results.